PENGARUH KOMPETENSI SDM, PENERAPAN SAP BERBASIS AKRUAL, SIMDA, DAN SISTEM PENGENDALIAN INTERN TERHADAP RELEVANSI LAPORAN KEUANGAN PEMERINTAH DAERAH - Sri Ayem; Idham Husen (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
This research was conducted to test the factors that affect the relevance of local government financial statements. The factors studied were the influence of Human Resources competencies, the application of the accrual-based government accounting standards, the regional management information system, and Internal Control System. The population that used in this study is the regional working units (SKPD) the that there inside Mayor’s Office Yogyakarta. The study sample was obtained from the structural officers, employees / staff the that performs the function of accounting / financial administration in their respective offices on SKPD, the that there inside Mayor’s Office Yogyakarta, then be obtained of the respondent as much 105 respondents. Collecting data in this study is to directly deploy questionnaires to the respondent. The data collected were processed using SPSS Version 17. The method used to test the hypothesis is multiple linear regression analysis. The results of this study indicate that : The influence of Human Resources competencies not the effect positive and significant on the relevance of local government financial statements, the application of the accrual-based government accounting standards the effect positive and significant on the relevance of local government financial statements, the regional management information system not the effect positive and significant on the relevance of local government financial statements, and Internal Control System the effect positive and significant on the relevance of local government financial statements.